PENGARUH FEED RATE DAN SPINDEL SPEED TERHADAP KEKASARAN PERMUKAAN THERMOPLASTIC NYLON MENGGUNAKAN CNC VMC 750 - zerano akbar, M Alfez; Firdaus, Firdaus; Suryana , Didi (Politeknik Negeri Sriwijaya, Indonesia, 2023)
Nowadays, working with production machines is very much needed in the manufacturing industry. The surface roughness produced by the machining process determines the quality of the workpiece components. Surface roughness can be influenced by factors, namely, feeding speed, cutting speed, and depth of cut so that these factors greatly affect the surface quality. Several conclusions can be drawn: Variations in Feed Rate and Spindle Speed ​​dosnt have an influence on the level or value of the surface roughness of the Nylon specimen. the smoothest or best is at Fr 400 mm SS 1910 rpm with a roughness value of 1.377 µm and the roughest at Fr 800 mm SS 636 rpm with a roughness value of 4.114 µm. at Fr 400,600,800 mm, SS 1910 rpm produces an average roughness of 1,505 m , At 400,600,800 mm, SS 1273 rpm produces an average roughness of 1,968 µm, At 400,600,800 mm ,SS 636 produces an average roughness of 3,301 µm.